Revisiting the “Imperative of Categories”: Women at Risk in Resettlement Practice - Schultz, Jessica (Refuge)

(untitled) (Centre for Refugee Studies, York University, 2026)
Refugee “women at risk” (WaR) have been prioritized since the late 1980s as candidates for third-country resettlement. Drawing on Macklin (1995), this article interrogates the logic and consequences of the WaR category. Through the lens of Norwegian practice, it shows how restrictive interpretations of UNHCR’s criteria and securitized resettlement processes reinforce a culture of disbelief and a focus on non-state protection by men. The application of WaR incentivizes family separation and perpetuates essentialist ideas about women’s vulnerabilities. While a broader category for gender-based risks can moderate WaR’s exclusionary effects, it similarly contributes to legitimizing harmful border regimes.